(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In this research, we provide a 5G-capable IoT infrastructure that optimizes spectrum and electricity. It uses energy harvesting or energy transfer to minimize its impact on the cellular network’s performance. The Internet of Things network comprises sensor nodes and a power-efficient cluster head that repurposes unused portions of the cellular frequency spectrum. The cluster leader is in charge of spectrum utilization, random sequencing of sensor nodes, or scheduling downtime for energy transfer. The cellular communication and transferred power from the cluster are converted into RF energy, which the sensor nodes then use. As long as the sensors have power, they will send the data they have acquired at the appointed time. Spectrum supply, energy availability, information transfer, and energy transfer all come into play as a result of the interaction between both the cellular and IoT network. This study demonstrates that, for a given amount of cellular traffic, an increase in the number of devices in the network leads to a multi-user gain due to the IoT network’s increased utilization and the broadcast aspect of the transfer of energy. The findings shed light on the kind of Internet of Things applications that might be feasible under various operational regimes.